Status Tanah Hasil Reklamasi: Studi Empiris Pasca Pengesahan Peraturan Cipta Kerja - Iwan Muri Susanto; Inge Dwisvimiar; Rani Sri Agustina (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
Generally, pre-reclamation issues are related to licensing issues, which are one-sided legal actions (one-sided will of the government), as well as the issue of reclamation land concession permits, which are two-sided legal actions (government and entrepreneurs). Not infrequently regulatory policies regarding reclamation intersect with each other between the authorities of the central and regional governments. Meanwhile, post-reclamation issues are related to the form of control and ownership of reclamation land, including management rights and land rights obtained from reclamation results. This research study aims to analyze the licensing authority and status of land reclamation results to the ratification of Law Number 6 of 2023 concerning Job Creation and empirical studies on PT Gandasari Energi. This research study uses a normative-empirical legal research approach, namely combining applicable norms with data suitability in the field by comprehensively examining legal norms and a case study approach. The results of the study show that the reclamation licensing authority at PT Gandasari Energi is based on Law no. 6 of 2023, is the attribution authority owned by 2 (two) stakeholders, namely the Governor who delegates his authority to the head of the Office of Investment and One-Stop Integrated Services (DPMPTSP) of Banten Province and the Ministry of Transportation through concession cooperation with Port operator units (KSOP ) As the authority for port activities that have not been exploited commercially.